Time-resolved X-ray radiography of through-thickness liquid transport in partly saturated needle-punched nonwovens - Wegele, Patrick; Yao, Zisheng ; 0000-0001-7970-2133; Tejbo, Jonas; Rogalinski, Julia K. ; 0009-0008-7133-619X; Rosén, Tomas; Groetsch, Alexander; Nygård, Kim; Asimakopoulou, Eleni Myrto ; 0000-0003-2127-373X; Villanueva-Perez, Pablo ; 0000-0002-4671-790X; Söderberg, L. Daniel (Experiments in Fluids, 2026)
Nonwoven fibre networks underpin filtration, insulation and geotextiles, where liquid uptake, redistribution and release govern performance. In needle-punched felts, barbed needles mechanically entangle fibres and partially reorient them towards the thickness direction (z), creating out-of-plane “pillars” and heterogeneity. While mechanical and structural consequences of needling are well documented, dynamic z-direction transport in partly saturated networks remains difficult to access due to opacity and sub-second timescales. Here we combine micro-CT (μCT) of dry structure with time-resolved X-ray radiography during droplet addition to quantify through-thickness transport as a function of saturation and needling intensity, using a compact Washburn-type descriptor for dynamics. Results show an exponential dependence of z-directional liquid transport on saturation, consistent with previous models for in-plane relative permeability of nonwoven networks. Additionally, increased needle-punch intensity reorients fibres towards the z-direction, forming preferential flow pathways that enhance through-thickness transport, even as single-phase permeability decreases. These findings underscore needle-punch as a key design parameter for tuning liquid transport in nonwoven fibre networks. The approach provides an experimental and modelling framework for dynamic, capillarity-driven transport in opaque fibrous materials.